TATA KELOLA TINGKAT LAYANAN SISTEM INFORMASI PEMESANAN TIKET MENGGUNAKAN KERANGKA KERJA COBIT 4.1 PADA ARNES SHUTTLE CABANG KOTA BANDUNG - R.Fenny Syafariani; Gilang Nandapratama (Sekolah Tinggi Teknik - PLN, 2015)
All the development of information systems and computer technology very fast. It can be seenin everyday life where people in this world are utilizing the computer as a tool to complete their job.Information systems are used to provide facilities for a company in general. And the special tofacilitate the service for booking tickets at Arnes Shuttle Branch Bandung.Information technology required by Arnes Shuttle is related to information technology ticketbooking system . The information system will allow a company to run its business processes . Butafter research by observation and interviews are still found weaknesses in the current system . Theproblems that exist in the ticket booking information system is the frequent occurrence of error orcan’t be processed that cause slow serviceFor the management of information systems need to service level governance informationsystem using the COBIT framework 4.1 (Control Objective for Information and Related Technology).